Determinan Penerimaan Pajak Penghasilan Badan: Studi Negara Amerika Latin - Listikarini, Dian Irsalina (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
Latin America as a region with great natural resource potential, still has a narrow tax base due to problems of law enforcement, tax incentives and tariff reductions. The corporate income tax that significantly increases revenue in the Latin America/LAC in 2019 around 3.7 percent of GDP is interesting to study. Therefore, this research was conducted to examine the determinants of corporate income tax revenue in the Latin American. This study uses panel data on 12 countries in Latin America in 2008-2018. The statistical method used is a quantitative method with multiple linear regression. Based on testing, the panel-corrected standard error estimation model is the best model. The results show that all independent variables simultaneously affect tax revenue. The variables of economic growth, FDI inflows, land area, and trade openness partially have significant positive effect on corporate income tax revenues. Meanwhile, the tax attractiveness index variable has significant negative effect on corporate income tax revenue in Latin American. Based on the results of this study, it is necessary to review the international trade policies in the Latin American because trade openness still tends to have no effect and even weaken the positive relationship between FDI inflows and corporate income tax revenues.